STUDY OF VESICULAR-ARBUSCULAR MYCORRHIZAL FUNGI IN THE SOIL SAMPLES OF THE NORTHERN KAZAKHSTAN - Yessenbayeva , A.E.; Ten , O.A.; Balpanov , D.S. (Eurasian Journal of Applied Biotechnology, 2016)
In the agricultural sector the VAM is a natural alternative to application of a great amount of fertilizers, primarily the phosphorous ones and can be used for the remediation of the disturbed natural ecosystems. According to the literature data the arbuscular mycorrhizae have a stimulating effect which results in a significant increase of the yield of agricultural crops. The VAM has a therapeutic effect by protecting the plants against the root pathogens. The VAM decreases a disease rate by means of the action of the following 2 mechanisms: 1) elimination of a pathogen by means of synthesis of the antibiotics or under a substrate competition; 2) induction of the immune reactions of a host plant. The VAM-fungi have a high adaptability to various environmental conditions. They develop in a wide range of the soil acidity, temperature, humidity and aeration. The article describes the method of isolation of the vesicular-arbuscular mycorrhizal fungi from the soil samples of the northern Kazakhstan. We obtained the enrichment cultures of the VAM fungi associated with the roots of sorghum. A VAM fungi-based fertilizer was developed on the basis of the obtained cultures and tested on one of the cereal grain cultures – barley. The efficiency of the VAM is determined by a plant response to a mycorhization expressed in a yield increase. This article describes the investigation and isolation of the VAM fungi from the soil samples of Kazakhstan.